Design of Education and Rehabilitation Center for Autism Children in Ternate City - Nurazizah Darwis,; Firdawaty Marasabessy,; Hery Purnomo, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Ternate City is one of the cities from North Maluku Province whose population density is so high, so it has the highest number of children with autism. The design location is in Ngade Village, South Ternate City. The design method is carried out in 3 stages. The first stage is a data collection technique in the form of literature studies and field observations. The second stage is the Analysis of Environmental, Human, and Building Aspects. The third stage is in the form of design concept results and building design products in the form of working drawings. The building of the Autism child education and rehabilitation center is a forum for the fulfillment of facilities and infrastructure for people with autism in Ternate City as facilities for handling services for children with autism, developing the talents of children with autism, as well as other functions as a medium for information and introduction about Autism disorders to the wider community. The Center for Education and Rehabilitation of Children with Autism answers the need for proper schools for children with autism in Ternate City. The space needs of building users follow the standards of facilities and infrastructure that are suitable for children with special needs (Autism). The concept of behavioral architecture implements the behavior of children with autism by prioritizing physical and psychic comfort factors to the creation of building conditions and environments whose atmosphere is healing, safe, calm and comfortable